2018
DOI: 10.1111/clr.13365
|View full text |Cite
|
Sign up to set email alerts
|

A novel methodological approach using superimposed Micro‐CT and STL images to analyze hard and soft tissue volume in immediate and delayed implants with different cervical designs

Abstract: Objectives:To study the hard and soft tissue volume after placing immediate (IMI) or delayed implants (DLI) with a triangular coronal macro-design (Test/T) or a conventional cylindrical design (Control/C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…This increase however, did not involve the soft tissue volume above the implant shoulder, hence suggesting the need of soft tissue grafting in the transmucosal area to attain an optimal tissue volume. 23 The observed reduction in tissue contours may be mainly related to the reduction in the width of the osseous ridge, which occurred in spite of having grafted the socket with DDBM-C. These findings are in agreement with those observed in a recent RCT using the same bone replacement graft, compared to non-grafting, which reported that grafting the gap significantly limited horizontal bone resorption, although a certain degree of bone resorption always occurred.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This increase however, did not involve the soft tissue volume above the implant shoulder, hence suggesting the need of soft tissue grafting in the transmucosal area to attain an optimal tissue volume. 23 The observed reduction in tissue contours may be mainly related to the reduction in the width of the osseous ridge, which occurred in spite of having grafted the socket with DDBM-C. These findings are in agreement with those observed in a recent RCT using the same bone replacement graft, compared to non-grafting, which reported that grafting the gap significantly limited horizontal bone resorption, although a certain degree of bone resorption always occurred.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the buccal bone volume lost after extraction was compensated by an increase in soft tissue volume below the implant shoulder. This increase however, did not involve the soft tissue volume above the implant shoulder, hence suggesting the need of soft tissue grafting in the transmucosal area to attain an optimal tissue volume …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In recent years, the superimposition of DICOM data from CBCT and STL methodology gave insights in experimental and clinical research to better understand the dynamics of tissue healing in a three-dimensional way. Furthermore, this technology allowed to discern the hard and soft tissue inter-play and the reciprocal role that they may have (Sanz-Martin et al, 2017;Sanz-Martin, Encalada, et al 2019;Sanz-Martín, Permuy, et al, 2018). Chappuis et al (2015), evaluating the fate of buccal soft and hard tissues 8 weeks after extraction and before delayed implant placement, observed that soft tissue profile did not follow the pronounced resorption pattern of the underlying bone anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…There are dentists who have used this superimposed method to obtain the implant position and the emergence contour of prosthesis, and suggested that the aesthetic outcome was satisfactory (Liu, Liu, Mao, & Tan, 2017). Recently, there was an animal experiment in which the optical scan data of the study model were superimposed with the micro-CT, and histological measurements indicated that the digital measurement had high accuracy and repeatability (Sanz-Martin et al, 2018). In clinical studies, researchers also measured the volume change of soft tissue around the implant and natural tooth, which proved the feasibility of this method (Fickl et al, 2009;Schneider, Grunder, Ender, Hammerle, & Jung, 2011;Windisch et al, 2007).…”
Section: Discussionmentioning
confidence: 99%